Characterization of fruticose lichen genus Stereocaulon from Sabah based on morphology, Chemo typing, and Molecular Typing - Jing-Kae LIM; Charles Santhanaraju Vairappan; Thor-Seng LIEW (Universiti Malaysia Sabah, 2025)
Lichens in the genus Stereocaulon are commonly found in high-elevation mountains in tropical regions. Taxonomy of Stereocaulon is always an ongoing topic discussed among lichenologists, especially for species-level identification due to polymorphism and chemical diversity of Stereocaulon. In this study, we examined Stereocaulon spp. from Mount Kinabalu, the highest mountain in Borneo (4095 m). A total of 42 Stereocaulon specimens were included in this study; 40 were newly collected between 1900 m and 3700 m a.s.l. along the summit trail of Mount Kinabalu, and two specimens from Mount Alab (1900 m) were previously published. We used integrative approaches to delimit the specimens into Operational Taxonomic Units (OTUs) based on macro-morphology, chemical profiles, and molecular phylogeny. Macromorphological characters, including apothecia (reproductive organ), phylloclade, pseudopodia and Cephalonia were examined, while chemical profiles were obtained from spot tests and High-performance thin-layer chromatography (HPTLC). A phylogenetic tree was constructed based on the ITS gene by using Bayesian and Maximum Likelihood analyses. A total of six Operational Taxonomic Units (OTUs) were identified and were provisionally named according to their diagnostic morphological and chemical characters, namely, RF (ramularia-fluorescence), RN (ramular-nonfluorescence), GF (granular-fluorescence), GN (granular-no fluorescence), RU1 (hamular-curved 1) and RU2 (ramularia-curved 2). The monophyly of each of the OTUs is supported by phylogenetic analysis. Due to lack of reliable identification keys and reference genetic data for this genus, we could not determine the species identities for the OTUs revealed in this study. Nevertheless, the findings of this study provide a baseline for future studies on the taxonomy of Stereocaulon species in Mount Kinabalu, integrating morphology, chemistry, and genetics. The implementation of high-performance thin-layer chromatography (HPTLC) profiles show potential for distinguishing samples. However, further research with more Stereocaulon samples from different taxa and regions is necessary to verify the reliability of this method.